Islamic Bank Performance and Macroeconomic Variables During Economic Turbulence - Maharani, Dian Putri; Roza, Fhadila; Wijayanti, Feny Gusti; Nopiah, Ririn (International Ecsis Association, 2024)
The study aims to analyze the effect of internal and external bank factors on the financial performance of Islamic banks during the Covid-19 pandemic. The external factors or macroeconomic factors consist of BI Rate and Inflation. The internal bank factors used are BOPO (Operating Expenses for Operating Income), CAR (Capital Adequacy Ratio), FDR (Financing to Deposit Ratio), NPF (Non-Performing Financing), and ROA (Return on Assets). A quantitative analysis is applied to assess the research construct by using a panel regression approach. The data used is sourced from Bank Indonesia and the Financial Services Authority for the observation period from 2019 - 2021. The findings show that external factors do not affect ROA in the long run and short run. Meanwhile, the internal factors BOPO and CAR significantly influence ROA, and NPF is having a significant impact only in the long run. The implications of this study show that Islamic banks need to strengthen operational efficiency, maintain capital adequacy, and implement good credit risk management in order to increase profitability sustainably, regardless of external fluctuations such as BI interest rates and inflation.